The incidence of prostate cancer is increased in patients with obstructive sleep apnea: Results from the national insurance claim data 2007-2014. Issue 6 (12th February 2021) - Lee, Eun Jung; Suh, Jeffrey D.; Cho, Jae Hoon
Abstract : Abstract: Some studies have demonstrated an increased risk of prostate cancer in patients with obstructive sleep apnea (OSA). However, the relationship is unclear and the results are conflicting. This study aims to investigate associations between OSA and prostate cancer using the Korea National Health Insurance Service database. A total of 152, 801 men (≥ 20 years of age) newly diagnosed with OSA between 2007 and 2014 were included. A control group of 764, 005 subjects was selected using propensity score matching by age and sex. The mean follow-up time was 4.6 years (range 2.3–6.9). The primary endpoint was newly diagnosed prostate cancer. The prostate cancer hazard ratio (95% confidence interval) was calculated for patients with OSA and compared to the control group. The incidence of prostate cancer among patients with OSA was significantly higher than that in controls (1.34 [1.23–1.49]). In particular, the incidence of prostate cancer was highest in patients aged 40–65 years (1.51 [1.32–1.72]). This study provides additional evidence for a link between OSA and prostate cancer.